Financiamento às empresas de micro, pequeno e médio portes uma análise do perfil da liberação e da distribuição regional dos recursos direcionados pelo BNDES - Torniziello Filho, Weber Luiz (2017)
The present work studies the distribution of credit resources by the National Financial System, focusing on the credit lines directed by the “Banco Nacional de Desenvolvimento Econômico e Social” (BNDES) between the years 2000-2014 to Micro, Small and Medium Enterprises. To that end, we have brought to light the discussion of the investment financing dynamics pointed out by Keynes, showing the role of finance, but highlighting the complexity of funding. Moving forward in this discussion, we have brought the elements postulated by Minsky about the dynamics of banks' performance, especially after the 1960s, showing their continuous performance, relating the search for capital appreciation, the security and liquidity relationship, and also the Dow's contribution to the spatial distribution of resources. The aim, therefore, is to verify if the state bank was able to reverse the logic of the banking system, which is to concentrate resources in more dynamic and economically integrated regions and in larger and / or capitalized agents. Thus, starting from a post-Keynesian perspective, we sought to understand how this dynamic occurred, especially in the post-2008 period, when the subprime crisis reversed expectations and, as a consequence, tended to reduce bank credit lines, especially in the sphere Private. However, although there was an improvement in the distribution of resources through a public bank in Brazilian regions that were not previously covered by these types of onlendings, we identified the continuity of the concentration of credit in the most dynamic regions of the country. For this observation, we created indexes that capped the proportion of credit - either through BNDES or via SFN through commercial banks and multiples - against the GDP of each Brazilian municipality, versus the HDI of these same municipalities, to carry out our analyzes. In the same way, we did for the Southeast and Northeast macro-regions, in order to counterpose these two locations and show the disparity, from the point of view of directing public policies, still existing.